Effect of gelatinization degree on emulsification capacity of corn starch esterified with octenyl succinic acid. (1st May 2022) - Lopez-Silva, Madai; Agama-Acevedo, Edith; Yee-Madeira, Hernani; Bello-Perez, Luis A.; Alvarez-Ramirez, Jose
Highlights: Partial gelatinization improved esterification of corn starch. Access to esterification reaction sites was enhanced by gelatinization. Partially gelatinized and esterified normal corn starch produced stable emulsions. Abstract: Normal corn starch (∼26% amylose content) was subjected to different degrees of extrusion-based pregelatinization (55, 75, and 95%) to improve the efficiency of octenyl succinic anhydride (OSA) esterification. The partial disruption of the native semi-crystalline structure was verified with X-ray diffraction and Fourier transform infrared analysis. It was found that partial gelatinization (pregelatinization) reduced the relative crystallinity, which is an effect that was magnified by OSA esterification. Polarized and scanning electron microscopies revealed gradual destruction of the starch granules, yielding a fraction of insoluble remnants for high gelatinization degrees. The emulsification index showed a marked increase of about 18% by single extrusion treatment. However, fully stable emulsions (emulsification index = 1.0) were obtained by dual extrusion-esterification treatment. The hardness of hydrogels was reduced by pregelatinization. Principal component analysis revealed that most starch characteristics were mutually interdependent and that the impact of gelatinization degree was independent of the impact of OSA esterification.